Different Influences of Negative and Neutral Emotional Interference on Working Memory in Trait Anxiety - Yang, Huifang; Li, Junqing; Zheng, Xifu (Frontiers in Psychology, 2021)
To examine the interaction of working memory(WM) type with emotional interference in trait anxiety, ERPs were measured in a combined WM and emotional task. Participants completed a delayed matching-to-sample task of WM, and emotional pictures were presented during the maintenance-interval. The results indicated that negative affect interfered with spatial WM; task-related changes in amplitude were observed in the late positive potential (LPP) and slow waves in both the high- and low-anxiety groups. We also found an interaction among WM type, emotion and trait anxiety such that participants with high levels of trait anxiety showed an opposite neural response to verbal and spatial WM tasks compared with individuals with low trait anxiety during the sustained brain activity involved in processing negative or neutral pictures in the delay phase. Our results increase our understanding of the influence of emotions on recognition and the vulnerability of those with trait anxiety to emotional stimuli.